Parental smoking exposure before and during pregnancy and offspring attention-deficit/hyperactivity disorder risk: A Chinese child and adolescent cohort study - Liu, Dong; Ren, Yaping; Wu, Tianfeng; Shen, Huiping; Yan, Peijing; Meng, Yu; Zhang, Qianlong; Zhang, Jun; Bai, Pinqing; Zhao, Jian (Frontiers in Public Health, 2022)
Background Previous studies revealed that maternal smoking exposure during pregnancy was an essential risk factor for offspring developing attention-deficit/hyperactivity disorder (ADHD). The impact of paternal smoking exposure 1 year before pregnancy on offspring ADHD risk is still unclear. Methods The present study included 2,477 school-age children and their parents from the Shanghai Child and Adolescent Health Cohort who had complete data for offspring ADHD diagnosis and parents' smoking exposure before and during pregnancy information. A multivariate logistic regression model and Firth's logistic regression model were used to determine the associations of paternal smoking and parental smoke exposure patterns before and during pregnancy with offspring ADHD risk. Results Children whose fathers smoked before pregnancy had a higher risk of developing ADHD [odds ratio (OR) = 2.59, 95% confidence interval (CI): 1.35–4.98] compared to those whose fathers had never been exposed to smoking. Similarly, parents who were exposed to smoking or second-hand smoke before pregnancy had 1.96 times (OR = 1.96, 95% CI: 1.19–3.22) more likely to have offspring with ADHD. Moreover, children whose parents were exposed to smoking both before and during pregnancy were 2.01 times (OR = 2.01, 95% CI: 1.29–3.12) more likely to develop ADHD. Conclusion Paternal smoking before pregnancy and parental smoking exposure 1 year ahead of and throughout pregnancy were all risk factors for offspring developing ADHD.